ПОСЛЕЛЕДНИКОВЫЕ ТЕКТОНИЧЕСКИЕ ДВИЖЕНИЯ И ФОРМИРОВАНИЕ ТЕРРАС ОЗЕРА ИМАНДРА (КОЛЬСКИЙ ПОЛУОСТРОВ) - Шварев С.В. (My University, 2003)
The series of postglacial terraces surround the lake Imandra. Terraces of relative height -3 - - 11 m are built up with one stratum of limnoglacial deposits of Late Quaternary age. The sediment texture is characterised by cross-bedding, flexures and synclinal folds. Accumulation was influenced by tectonic movements, which were manifested in the inclination of terraces surface, and in splitting of initial surface in several levels. Terraces with relative height 0-3 m were built up with Holocene lacustrine deposits. Two stages of Holocene accumulation took place under the conditions of low tectonic activity. At one stage high socle terrace with thin stratum of lacustrine sediment was formed; at another - low accumulative terrace with horizontal lamination of deposits. Morphotectonics of Lake Imandra basin gives an evidence of direct reflection of neotectonic structure in the relief. Relative movements of small blocks come to first meters, while the whole amplitude of neotectonic movements in the basin reaches up to tens of meters.
Keywords: Holocene; 551.435.322(470.21); Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен